The risk of childhood brain tumors associated with delivery interventions: A Danish matched case-control study. (February 2022) - Yeh, Karen W.; He, Di; Hansen, Johnni; Carpenter, Catherine L.; Ritz, Beate; Olsen, Jorn; Heck, Julia E.
Abstract: Background: Head trauma has been associated with increased brain tumor risk in adults. Instrument assisted delivery can be a cause of head trauma in newborns. The goal of this study was to determine if instrument-assisted deliveries influenced the odds of childhood brain tumors in Denmark. Methods: We conducted a matched case-control study of childhood (<20 years) brain tumors in Denmark born between 1978 and 2013 and diagnosed 1978–2016. A total of 1678 brain tumor cases were identified and 25 controls were matched to each case based on the child's sex and birth date (N = 40, 934). Conditional logistic regression was used to estimate effects (odds ratios (OR) and 95% confidence intervals (95%CI)) for variables of interest. Results: Compared to children birthed by spontaneous vaginal delivery, children who later developed ependymomas (N = 118) had a greater likelihood of having experienced vacuum assisted deliveries (OR=1.74, 95% CI 1.02–2.96). Forceps use was low, and declined across the study period. We did not observe an overall increase in all CNS tumors (combined) with either vacuum delivery (OR=0.99, 95% CI 0.84–1.18) or forceps delivery (OR=1.26, 95% CI 0.78–2.03). Conclusion: Our findings suggest an association between vacuum assisted deliveries and ependymomas. Highlights: The overall association in childhood CNS tumors with vacuum delivery was null. All childhood CNS tumors with forceps delivery had null associations. Children had an increased risk of ependymoma following a vacuum assisted delivery.